2011
DOI: 10.2340/00015555-1173
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Neurophysiological Methods in Itch Research: Long-latency Evoked Potentials after Electrical and Thermal Stimulation in Patients with Atopic Dermatitis

Abstract: The aim of this study was to examine the findings of innovative neurophysiological methods of itch research. Short-latency and pain-related somatosensory-evoked potentials after electrical stimulation, as well as long-latency evoked potentials after thermal stimulation were studied in 38 patients with atopic dermatitis (AD) and 26 healthy volunteers. Quantitative Sensory Testing of thermal perception was performed in 22 patients with AD from the main AD group and in 15 healthy volunteers. Brain hyperactivity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…We measured the WDT and HPT bilaterally at the upper back, lateral arms and shins, as cutaneous amyloidosis typically occurs over these areas. We found that the WDT was elevated in patients with PLCA, but the raised HPT was not statistically significant, similarly to a previous study in AD . HPT thresholds can be less accurate in diagnosing SFN, as pain responses are significantly affected by cognitive and emotional states of patients .…”
Section: Discussionsupporting
confidence: 86%
“…We measured the WDT and HPT bilaterally at the upper back, lateral arms and shins, as cutaneous amyloidosis typically occurs over these areas. We found that the WDT was elevated in patients with PLCA, but the raised HPT was not statistically significant, similarly to a previous study in AD . HPT thresholds can be less accurate in diagnosing SFN, as pain responses are significantly affected by cognitive and emotional states of patients .…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, our group found an even higher sensory threshold to electric current stimulation in patients with atopic dermatitis or psoriasis than in healthy volunteers, although no significant differences were found between subjects with atopic dermatitis and psoriasis [43]. Our results are in accordance with the observations made by Yudina et al, who documented elevated thermal thresholds in patients with atopic dermatitis [40].…”
Section: Measurement Of Itch Thresholdsupporting
confidence: 56%
“…However, it was also suggested that subjects with chronic pruritus might also be more sensitive to itchy stimuli due to lowering of itch threshold at the periphery [37][38][39][40]. For instance, it was observed that tactile threshold in patients with nodular prurigo was lower than in controls and this abnormality was reversed by capsaicin, suggesting the involvement of neuropeptides, mainly substance P [37].…”
Section: Measurement Of Itch Thresholdmentioning
confidence: 95%
“…Unpleasant sensations, such as itching, pain and paraesthesias, likely influence impaired sexual health beyond the lesions themselves. Sensory disorders are very frequent in patients with AD . Atopic patients frequently have hyperknesis (an increased perception of itch) and alloknesis (a touch‐evoked itch) .…”
Section: Discussionmentioning
confidence: 99%
“…Sensory disorders are very frequent in patients with AD. 13,14 Atopic patients frequently have hyperknesis (an increased perception of itch) and alloknesis (a touch-evoked itch). 25 Although it has been never explored, we believe that these disorders seriously limit patient sexual desire and whole body perception in men as well as in women, especially of the genital area and the breasts.…”
Section: Discussionmentioning
confidence: 99%